Novel Genotype in Two Siblings with 5-α-reductase 2 Deficiency: Different Clinical Course due to the Time of Diagnosis - M Kocova; D Plaseska-Karanfilska; P Noveski; M Kuzmanovska (Macedonian Academy of Sciences and Arts / Sciendo, 2019)
Steroid 5-α-reductase-2 (5-ARD) deficiency is a result of mutations of the SRD5A2 gene. It causes the disorder of sexual differentiation (DSD) in 46,XY individuals with a variable genital phenotype. We present two siblings with female external genitalia at birth and bilateral inguinal testes, raised as females. These are the first molecularly characterized patients from the Republic of North Macedonia (RN Macedonia) with a different clinical course due to the time of the diagnosis. Diagnosis of Patient 1 was based upon the detection of bilateral inguinal testes and testosterone/dihidrotestosterone ratio. Sex reversal was initiated by testes removal at the age of 20 months. Breast implantation and vaginoplasty were performed in adolescence and the girl is comfortable with the female sex. Her sibling, Patient 2, raised as a girl, was clinically assessed at 11.5 years due to the growth of phalus, deep voice and Adam's apple enlargement. No change of gender was accepted. Complex molecular analysis including multiplex quantitative fluorescent polymerase chain reaction (PCR) screening for sex chromosome aneuploidies and SRY presence, Sanger sequencing combined with multiplex ligation-dependent probe amplification (MLPA), microarray-based comparative genomic hybridization (aCGH), and real-time PCR analysis for detection of exon copy number changes confirmed a novel c.146C>A (p.Ala49Asp) point mutation in the first exon inherited from the mother, and complete deletion of the first exon and adjacent regions inherited from the father. Novel genotype causing 5-ARD is presented. Genetic analysis is useful for the diagnosis and timely gender assignment in patients with 5-ARD. However, final gender assignment is difficult and requires combined medical interventions.